Stress level of nursing students due to online learning during the covid-19 pandemic - Pebriani, Sintiya Halisya; Syafei, Abdul; Mardiah, Mardiah (Media Keperawatan Indonesia, 2021)
Changes in learning methods to online learning due to the Covid-19 pandemic have an impact on the psychology of students. Constraints related to the implementation of online learning cause students to experience stress. This study aims to investigate the effect of online learning on stress levels in nursing students at STIK Siti Khadijah Palembang. The research was descriptive correlation design with cross-sectional approach, the total sample was 230 students with total sampling technique. Data were collected through online-based questionnaires (google form), namely the online learning constraints questionnaire and the Perceived Stress Scale (PSS-10). Data analysis using the chi-square test. The results showed that most of the students (50.9%) experienced enough problems in online learning and almost all students (90.9%) experienced moderate stress, statistical tests showed that there was an effect (p = 0.007) of online learning with stress levels on nursing students. The obstacles that students feel during online learning such as starting to feel bored, weak internet network, limited internet quota, difficulty concentrating and understanding the material, many lecture assignments, lack of understanding of electronic media are stress triggers for students, so it can be concluded that there is an effect of learning online during the Covid-19 pandemic with stress levels in nursing students.